Strategi Promosi Kesehatan terhadap Partisipasi Masyarakat dalam Pencegahan Diare pada Anak Balita - Endang Maryanti; Indah Anggraini; Sri Lasmawanti; Fahmashufyani Fahmashufyani; Muhammad Crystandy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the health promotion strategy for community participation in preventing diarrhea in children under five in the working area of the Tomuan Siantar Public Health Center. The method used is quantitative observational with a cross-sectional approach. The results showed that the value of p advocacy was 0.001, social support was p = 0.008, and community empowerment was p = 0.005. In conclusion, advocacy, social support, and community empowerment influence community participation in preventing diarrhea in children under five in the working area of the Tomuan Health Center. Keywords: Toddlers, Prevention of Diarrhea, Promotion Strategy